2023
DOI: 10.1108/ramj-09-2022-0145
|View full text |Cite
|
Sign up to set email alerts
|

Inventory management systems of small and medium enterprises in Bangladesh

Abstract: PurposeInventory is a crucial part of a systematic supply chain of a business. Small firms mostly neglect inventory management (IM) by accumulating excessive inventory for a time. The study aims to examine the IM practices of small and medium enterprises (SMEs) in Bangladesh.Design/methodology/approachThe study applied a qualitative case study design. Data were collected from ten SME owners in Bangladesh. The study employed a purposive sampling technique to collect data. This study used semi-structured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Exploring the influence of the regional context on the productivity and competitiveness of individual manufacturing firms in Spain, M.K. Alam et al proved the relationship between them and confirmed that enterprises achieve higher productivity growth due to their location in more competitive regions (Alam et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the influence of the regional context on the productivity and competitiveness of individual manufacturing firms in Spain, M.K. Alam et al proved the relationship between them and confirmed that enterprises achieve higher productivity growth due to their location in more competitive regions (Alam et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the application of digital technologies by small and medium enterprises (SMEs) in Bangladesh, a qualitative research approach is employed, involving in-depth interviews with 10 participants (Alam et al, 2023;Thakur and Alam, 2022). The participant selection involves purposive sampling to ensure diverse representation across industries and business sizes (Alam, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The study employed a qualitative case study method to attain the research objective. Data has been collected through semi-structured interviews from ten respondents (Alam et al, 2023;Thakur et al, 2022) as data is saturated due to no new findings (Alam, 2021). The participant selection involves purposive sampling to ensure diverse representation across industries and business sizes.…”
Section: Methodsmentioning
confidence: 99%